Spring triticale yield and its stability depending on the genotype and environmental conditions - В. К. Рябчун; В. С. Мельник; Т. Б. Капустіна; О. Є. Щеченко (Plant Varieties Studying and Protection)
Purpose. Assessing stability of yield formation of complex-valued varieties and lines of spring triticale under conditions and of different years of their growing. Identifying the best genotypes for yield potential, plasticity and stability. Methods. Ontogenetic, statistical and mathematical analyses. Results. Adaptive capacity and breeding value of spring triticale varieties and lines was established. Methods of breeding and parentage of the best samples were analyzed. Comparison of yields under conditions in of different years of growing allowed to identify genotypes with high yield potential – ‘ЯТХ 38-14’, ‘ЯТХ 61-14’, ‘ЯТХ 62-14’, with stable yields – ‘ЯТХ 17-14’, ‘Boryviter kharkivskyi’, ‘ЯТХ 43-14’, ‘Gusar kharkivskyi’, drought resistance ones – ‘ЯТХ 37-14’, ‘ЯТХ 43-14’, ‘ЯТХ-64-14’. The genotypes ‘Lebіd kharkіvskyi’, ‘ЯТХ 38-14’, ‘ЯТХ 62-14’ appeared to be more plastic. These samples may be used of hybridization to improve yield. Conclusions. The most promising to production and breeding are the lines ‘ЯТХ 17-14’, ‘ЯТХ 64-14’, ‘ЯТХ 37-14’, ‘ЯТХ 43-14’ (their average yield 4,27–4,48 t/ha) and varieties ‘Zlit kharkivskyi’, ‘Boryviter kharkivskyi’, ‘Gusar kharkivskyi’, ‘Darkhliba kharkivskyi’, which have high adaptive capacity combined with high productivity. They are valuable for use as a starting material in breeding for adaptability.